Research and Design of a Wing-Wall-Free Guardrail in Transition Between the Subgrade and the Bridge - Shen, Linlin; Hu, Ran; Wang, Tingyu (Frontiers in Materials, 2022)
Considering the difficulty and high cost of guardrail installation in the transition between the highway subgrade and the bridge, this paper proposes a wing-wall-free guardrail based on comprehensive research. It has carried out a performance analysis of material Q690 before proposing the scheme. It is found that this type of material has high yield strength and tensile strength, as well as high plasticity. Accordingly, the guardrail structure of the transition section of the wing-wall-free guardrail is designed, and the DYNA numerical simulation is carried out to optimize the structure. Moreover, vehicle crash tests are used to verify the performance of the newly designed guardrail. The results of the above-mentioned research methods are as follows: the vehicle crash tests show that the wing-wall-free guardrail can reach a protection level of Grade SB, with a collision energy of 280 KJ. All performance indicators meet the industry standards. The guardrail can be used in the transition between W-beam subgrade guardrails and concrete or combined bridge barriers. This proposed guardrail is beautifully designed with low cost and great conveniency for installation and maintenance.